A Survey on Availability and Scalability Requirements in Middleware Service Platform - Varsha, V; Ali, Anooja (International Journal of Computer Sciences and Engineering, 2025)
Middleware is a software that resides on top of the operating system. It provides a development environment to the applications on top of it. It is used in diverse areas like distributed systems; networks embedded systems and so on. In telecommunication industries, middleware is also used to provide platform management functions such as context management, fault management, process and node management and so on. Availability and scalability play an important role in these industries that are customer oriented. This paper is a survey on how middleware based on symmetric multiprocessing and cluster systems provide better availability and scalability.